2004
DOI: 10.1302/0301-620x.86b3.14643
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted knee arthroplasty versus a conventional jig-based technique

Abstract: We have compared a new technique of computer-assisted knee arthroplasty with the current conventional jig-based technique in 70 patients randomly allocated to receive either of the methods. Post-operative CT was performed according to the Perth CT Knee Arthroplasty protocol and pre- and post-operative Maquet views of the limb were taken. Intra-operative and peri-operative morbidity data were collected and blood loss measured. Post-operative CT showed a significant improvement in the alignment of the components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
302
3
12

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 444 publications
(331 citation statements)
references
References 12 publications
14
302
3
12
Order By: Relevance
“…All 11 of the surgeons participating in the study registered landmarks that tended to overly externally rotate the femoral component relative to the true epicondylar axis. Chauhan et al, in a cadaver study and a followup clinical evaluation, demonstrated excessive external rotation of the femoral component relative to the epicondylar axis identified by computed tomographic scanning [7,8]. Stockl et al [38] compared a series of TKAs performed with standard instrumentation versus CAS and evaluated the femoral component position relative to the epicondylar axis using postoperative computed tomography scans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All 11 of the surgeons participating in the study registered landmarks that tended to overly externally rotate the femoral component relative to the true epicondylar axis. Chauhan et al, in a cadaver study and a followup clinical evaluation, demonstrated excessive external rotation of the femoral component relative to the epicondylar axis identified by computed tomographic scanning [7,8]. Stockl et al [38] compared a series of TKAs performed with standard instrumentation versus CAS and evaluated the femoral component position relative to the epicondylar axis using postoperative computed tomography scans.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve of 20 knees using epicondylar referencing were rotated internally from the position determined by the planning software before initiation of bone cuts. The tendency for CAS systems to externally rotate the femoral component when epicondylar referencing is used has been documented in previous studies using a variety of systems [7,8,35,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although computer-assisted navigation has been used in craniofacial surgery, joint arthroplasty, trauma, and spine surgery [1,4,7,8] for some time, its application in orthopaedic bone tumor surgery is more recent [2,3,5,6,9]. To date, there is no software designed specifically for surgery on long bone and pelvic tumors.…”
Section: Introductionmentioning
confidence: 99%
“…However, some authors agree this objective may not be practically obtainable in every TKA [15]. Satisfactory position of a TKA prosthesis is commonly accepted to be an alignment within 3°from this ideal [1,6,7,12,17,18,22,23,28,33]. Aseptic loosening of the prosthesis has been reported to be more common in knees implanted in an alignment greater than 3°varus [26].…”
Section: Introductionmentioning
confidence: 99%